Dental Disease Treatment In The Tib Manuscript Mss2515 Via Halal Material Usage - Ahmad Bazli Ahmad Hilmi; Nazariyah Yahaya; Liyana Amalina Adnan; Zulkarnin Zakaria; Muhammad Hakim Kamal; Nur Nadia Fadhlina Daman Huri; Nurdalila A’wani Abdul Aziz (USIM Press, 2025)
Indexed